1999
DOI: 10.1116/1.581659
|View full text |Cite
|
Sign up to set email alerts
|

Spectroellipsometric characterization of plasma-deposited Au/fluoropolymer nanocomposite films

Abstract: Articles you may be interested inEffects of ion energy on the crystal size and hydrogen bonding in plasma-deposited nanocrystalline silicon thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
(23 reference statements)
0
29
1
Order By: Relevance
“…It is well known that SPR activity depends strongly upon the morphology of the nanoparticles, namely the size and shape of the metal clusters (Lee et al, 1999;Manera et al, 2008;Dalacu & Martinu 1999 ). Considering a global analysis, the same three groups of samples are clearly defined in the morphological and optical results.…”
Section: Optical Propertiesmentioning
confidence: 84%
See 1 more Smart Citation
“…It is well known that SPR activity depends strongly upon the morphology of the nanoparticles, namely the size and shape of the metal clusters (Lee et al, 1999;Manera et al, 2008;Dalacu & Martinu 1999 ). Considering a global analysis, the same three groups of samples are clearly defined in the morphological and optical results.…”
Section: Optical Propertiesmentioning
confidence: 84%
“…SPR is manifested as a distinct peak in the absorbance spectrum (Lee et al, 1999, Torrell et al, 2010c, and has been reported in several nanocomposite materials through the localization of an absorbance band on the visible wavelength range (Takele et al, 2006;Dalacu & Martinu 1999;Lee et al, 1999, Manera et al, 2008Zakrzewska et al, 2003;J. Vosburgh & Doremus 2004.).…”
Section: Optical Propertiesmentioning
confidence: 99%
“…This type of effect can be easily observed experimentally using films deposited by simultaneous RF sputtering of a gold target and plasma polymerization of a fluorocarbon monomer which has been added to the gas mixture. 22 The amount of fluoropolymer incorporated within the growing film can be controlled by the glow discharge parameters. The effect of a 10% fluoropolymer content is shown in Figure 4b, demonstrating a similar decrease in 3[£co,e] as predicted by the EMA model for voids.…”
Section: Thin Filmmentioning
confidence: 99%
“…In recent years, substantial progress has been made applying these films in applications ranging from optical waveguides, [1,2] optical filters and coatings, [3][4][5][6][7][8][9] photorefractive materials, [10,11] low-dielectric constant and low-refractive index materials, [12][13][14] display devices, [15] nonlinear optics, [16] light-emitting materials, [17] optical information recording, [18] and solar energy conversion. [19] Plasma polymerization (PP) of fluorine-containing materials has received special attention because these polymeric films possess a low dielectric constant and refractive index in addition to low surface energy, low coefficient of friction, low permeability constant, and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%